Historical trends in reported survival rates in patients with hypertrophic cardiomyopathy. Issue 6 (10th October 2005) - Elliott, P M; Gimeno, J R; Thaman, R; Shah, J; Ward, D; Dickie, S; Tome Esteban, M T; McKenna, W J
Abstract : Objective: To determine the range of survival rates of patients with hypertrophic cardiomyopathy (HCM) by comparing and contrasting the natural history of a cohort of patients seen between 1988 and 2002 with that of other published series. Methods: 956 adult (⩾ 16 years old) patients with HCM (572 men, mean (SD) age 42 (15) years, range 16–88) were evaluated by ECG, Holter, exercise testing, and echocardiography. Patient characteristics and survival data were compared with those in natural history studies from referral and non-referral centres published between 1960 and January 2003. Results: The duration of follow up was 69 (45) months. 120 (12.6%) patients died or underwent cardiac transplantation. Sudden cardiac death (n  =  48) was the most common mode of death. The annual rate of sudden death or implantable cardioverter-defibrillator discharge was 1.02 (95% confidence interval (CI) 0.76 to 1.26). Annual rates for heart failure death or transplantation and stroke related death were 0.55% (95% CI 0.37% to 0.78%) and 0.07% (95% CI 0.02% to 0.19%), respectively. When studies published within the last 10 years of the study period were compared with earlier reports, the size of individual study cohorts was larger (309 (240.6) v 136.5 (98.8), p  =  0.058) and the proportion with severe functional limitation NYHA class III/IV lower (12.4% v 24.8%, p < 0.0001), and fewer patients underwent septal myotomy-myectomy (5.2% v 18.7%, p < 0.0001). Published sudden death rates over the last 10 years were lower than previously published figures (median 1.0% (range 0.1–1.7) v 2.0% (0–3.5)). Conclusion: Published survival rates in HCM cohorts have improved progressively over the past 40 years. In the modern era the prevalence of disease related complications is similar in all reporting centres.